IMPLEMENTASI TEKNOLOGI GOOGLE APPS SCRIPT DAN PHP DALAM OTOMATISASI PENGELOLAAN DATA DAN PEMBUATAN DOKUMEN KERJA SAMA (OIA UNKRISWINA) - Fajar Hariadi; Riwa Rambu Hada Enda; Fajar Indra Prasetyo; Dhea Ananda Putri Bangu (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
The management of cooperation documents in higher education institutions requires efficiency, accuracy, and ease of access. However, at the Office of Institutional Advancement (OIA) of Wira Wacana Christian University Sumba, the process of preparing legal documents such as MoU, IA, and PKS is still carried out manually. This condition causes high workloads, the risk of input errors, and difficulty updating documents that are repetitive. To answer these problems, an automation system based on PHP and SQLite was developed that allows users to generate documents instantly through filling in document numbers and selecting partners and implementers. Google Apps Script is also used to deploy cooperation data to the relevant unit Spreadsheet automatically without manual intervention. The system is built with a simple waterfall approach: needs analysis, form generator design, and data automation script integration. The test results showed a reduction in document creation time of up to 70% and a reduction in input errors. In conclusion, this system is able to increase the efficiency, accuracy, and responsiveness of cooperation administration at OIA Wira Wacana Christian University Sumba.